Relations among transepithelial sodium transport, potassium exchange, and cell volume in rabbit ileum (The Rockefeller University Press, 1976)
The relation between active transepithelial Na transport across rabbit ileum and 42K exchange from the serosal solution across the basolateral membranes has been explored. Although 42K influx across the basolateral membranes is inhibited by ouabain and by complete depletion of cell Na, it is not affected when transepithelial Na transport is abolished (i.e. in the presence of an Na-free mucosal solution) or stimulated (i.e. when glucose or alanine is added to the mucosal solution). We are unable to detect any relation between the ouabain-sensitive Na-K exchange mechanism responsible for the maintenance of intracellular Na and K concentrations and active transcellular Na transport. In addition, the maintenance of cell volume (water content) does not appear to be dependent upon transepithelial Na transport or the ouabain- sensitive Na-K exchange pump. Although the results of these studies cannot be considered conclusive, they raise serious questions regarding the role of the Na-K exchange pump, located at the basolateral membranes, in active transepithelial Na transport and the maintenance of cell volume.